PENGARUH TEKNOLOGI INFORMASI, SALING KETERGANTUNGAN, KARAKTERISTIK SISTEM AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL (Studi Kasus : Perusahaan Manufaktur Di Semarang) - NURPRIANDYNI, AJENG; SUWARTI, TITIEK (Benefit: Jurnal Manajemen dan Bisnis, 2011)
This research tries to examine the impact of Information Technology and Interdependence to the Managerial Perfomance. There is Managerial Accounting System as the intermediation variable. The object of this research are the manufactures managers in Semarang. By purposive sampling technique this research choose 274 respondens. To analyze the data, this research uses validity and realibilty test and multiple regression analysis to examine the impact of the independence variables to the dependent variables. This research finds that Â Information Technology and Interdependence partially have a positive effect to the Managerial Accounting System. Beside that the Information Technology and Interdependence partially have a positive impact to the Managerial Perfomance. But the Managerial Accounting System is not the intermediation variable between Information Technology and Interdependence to the Managerial Perfomance